Using particle monitors to minimise Cryptosporidium risk - Hamilton, Paul (Cranfield University, 2002)
Over the last two decades, there bas been much interest in whether particle counters hold any significant benefit over conventional nephelometric turbidimeters in monitoring potable water treatment processes. Southern Water, which supplies drinking water to two million customers living in Kent, Sussex, Hampshire and the Isle of Wight first used particle counters at one of its works in 1992. This study presents the key results of a three-year study, conducted in conjunction with Cranfield University to find the most beneficial use of these monitors, so that a sensible investment can be made. This study comprised a series of monitoring trials, conducted at different ground and surface water treatment works. In many instances,. there was a strong similarity between turbidity and particle count trends, effectively making one of monitors redundant However, particle counters were shown to be beneficial in three ways: (a) they could be more sensitive to changes in water quality at low turbidities (below 0.1 NTU), (b) they could be more sensitive to changes associated with larger particle sizes and ( c) they could also provide useful information on particle size distribution. This issue of monitor sensitivity bas been analysed using a regression model built from experimental data For a given water sample, this model predicts how many more times sensitive particle counters will be, in detecting changes in water quality, compared to nephelometric turbidimeters. This indicated that whereas turbidimeters typically 'flat-line' at low values, particle counters are frequently more sensitive and so can be used as a fine-tuning optimisation tool below 0.1 NTU. However, this sensitivity is also proportional to the particle size distribution of the sample; particle counters are more suited to samples containing a high proportion of large particles (> 1 0µm). This explains why particle counters are not always 'more sensitive' below 0.1 NTU. Although no links could be found between particle counts (and turbidity) and Cryptosporidium oocysts, it appears that if oocysts are present in the raw water then inferior particle removal across a treatment process can lead to increased risk. Cryptosporidium oocysts were found even in very low turbidity (<0.1 NTU) treated water samples. This shows the need for fine-tuning treatment processes below 0.1 NTU and highlights a potential optimisation role for particle counters. The study concludes, however, that particle counters are best used as an optional process research/optimisation tool only: turbidimeters remain the preferred monitor for process control Indeed, the study finds no overwhelming evidence to justify the permanent installation of particle counters at treatment works. However, an increased use of portable particle counters in optimisation work is recommended. Consideration is given to other practical concerns such as where and how to use particle counters and what parameters to measure. The value of particle counters' sizing ability has also been assessed. In addition to sensitivity modelling, particle size distribution data revealed a large difference in the volume of particles passed by two sludge treatment plants. The study concludes that, where particle counters are used, there may be some value in monitoring particle size distribution using a particle size ratio or a similar statistic.